The pandemic's sustainability windfall: a case study of COVID-19 restrictions on electricity demand patterns and sustainable development goals - Heidarnejad, Parisa; Genceli, Hadi; Asker, Mustafa; Yumurtaci, Zehra (INDERSCIENCE ENTERPRISES LTD, 2024)
In this paper, the pattern of daily electricity demand mid- and post-pandemic eras relative to 2019 was investigated for Turkey and the total reduction of 9% in electricity demand from April to July 2020 in comparison to the same period in 2019 was monitored. Also, as a result of public behaviour changes, the electric demand of the service sector dropped by about 5.9%, 28.4%, 6.8%, and 5.8% during the first, second, third, and fourth quarters of 2020 in comparison to 2019. The electricity load was transferred from the service sector to the household sector in all four quarters of 2020. Eventually, the phasing out of measures on July 1, 2021, the electricity consumption of the service sector during the second half of the year improved to 31.11 TWh from 3.09 TWh during the same period in 2020. On the other hand, to comprehend the socio-economic effects of the pandemic, the variation of four indicators of sustainable development goals during the last 20 years was assessed and discussed for world, the UAS, OECD countries and Turkey.
Keywords: COVID-19 pandemic; electricity demand; lockdown; social behaviour; sustainable development; Turkey; Environmental Sciences & Ecology